PARTISIPASI MASYARAKAT DI SEKITAR HUTAN DALAM PROGRAM PERHUTANAN SOSIAL - Ida Rosada; Annas Boceng; Erni Azis (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2021)
The purpose of this study was to identify the implementation of the Social Forestry (SF) Program at the HKm Forest Farmer Group in Balusu District, Barru Regency, identify and analyze the level of community participation around the forest in the implementation of the social forestry program at the HKm Forest Farmer Group in Balusu District, Barru Regency and analyze the factors involved influencing the participation of communities around the forest in the implementation of SF programs at the HKm Forest Farmer Group in Balusu District, Barru Regency.This research was conducted. The research location was carried out in Balusu District, Barru Regency, South Sulawesi Province in the SF Program at the KTH HKm Sero and Sarewe Groups. While the time needed to conduct this research is 2 (two) months, namely August to September 2020. The population in this study were all members of KTH HKm in Balusu Subdistrict totaling 82 people, consisting of 45 KTH Sero, and KTH Sarewe. as many as 37 people. The sampling method was carried out by using the census method or taking all members of the HKm forest farmer group in Balusu District.The research data analysis method is using the method of effectiveness analysis, qualitative descriptive analysis, percentage analysis and multiple linear analysis.Therefore, to increase community participation in the management of hkm in Balusu sub-district, new regency, it is hoped that farmer groups need to be more active in assisting the government through the Forestry Service in developing Community Forestry (HKm) development programs in Balusu District, Barru Regency.